In honor of the anniversary of Professor Juan Bartolomé: from magnetism in materials to nanostructures - Ibarra, M. R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2024)
Introduction My arrival at the University of Zaragoza from the University of Granada to conduct my doctoral thesis under the supervision of Professor Agustín del Moral marked my introduction to new technologies, particularly access to low temperatures. Professor Domingo González introduced me to and facilitated my access to liquid helium. My interaction with these cryogenic and high-vacuum technologies was guided by Professor Juan Bartolomé, to whom I wish to dedicate a few lines summarizing a parallel trajectory in the evolution of our research from bulk materials to nanostructures over the last two decades. 2. Rare-earth intermetallic permanent magnets The technique for measuring magnetoelastic properties that I developed in the magnetism laboratory enabled our first collaboration, in which we observed the strong magnetoelastic contribution in the phase transitions of KMnF3 perovskites [1]. The discovery of permanent magnets based on rare earths (RE2Fe14B) sparked our interest, leading to our participation in European projects and resulting in a fruitful collaboration. Among other studies, we investigated magnetostrictive distortions, whether spontaneous or induced by magnetic fields [2]. This collaboration was part of the European project Concerted Action in Permanent Magnets (CEAM) [3], under which various RE-Fe-B-based alloys were studied. The significant impact on research into rare-earth intermetallic compounds and oxides, mainly in manganites, was due to the use of neutron diffraction and spectroscopy techniques. In this area, Professor Bartolomé played a crucial role in bridging our institutions with the Laue-Langevin Institute (ILL) in Grenoble. Spectacular results were obtained, such as the observation of “magnetic polarons” quasiparticles in mixed-valence manganites responsibles for the colossal magnetoresistence [4]. Up until the first decade of this century, the framework for scientific contributions at the Institute of Materials Science of Aragon (ICMA), a joint research center of the University of Zaragoza and CSIC, focused on the study of bulk materials due to the lack of microscopic and nanometric characterization resources. 3. The arrival of new infrastructures This situation evolved with the arrival of new infrastructures. They were provided by the creation of the Institute of Nanoscience of Aragon (INA). The INA was established in 2003 with the aim of becoming a reference center for research in nanoscience and nanotechnology, with the goal of establishing scientific infrastructures in a framework of transition from research on bulk materials to nanostructured materials. It emerged as an initiative to consolidate and enhance the research already being carried out at the University of Zaragoza in these emerging areas. This center focused on strategic areas such as nanofabrication, characterization of nanomaterials, nano-chemistry, and the applications of nanotechnology in biomedicine, electronics, and energy. One of the most impactful outcomes of this new scenario was the establishment of new scientific infrastructures within the framework of the Laboratory of Advanced Microscopy (LMA), featuring the most advanced aberration-corrected transmission electron microscopes. This represented a qualitative leap in terms of the capabilities for characterization and fabrication of nanostructures. The LMA was established as a Singular Scientific Facility (ICTS) at the national level, empowering the initial infrastructures of the INA: – Ultra-high resolution microscopy with two TEM microscopes with spherical aberration correctors (image and energy). They enabled significant advances in the characterization of materials at the nanometric and even atomic levels: their morphology and chemical composition. – Micro and nanolithography in a clean room: Optical lithography combined with electron beam lithography enabled the design of nanostructures and nanodevices. The combined electron and ion beam microscopes greatly boosted the growth of metallic, insulating, and superconducting nanostructures in situ using metal-organic precursor gases. – Local probe microscopy: Three ultra-high vacuum scanning tunneling microscopes (STM) have driven the recognition and fabrication of molecular and atomic structures for the study of new magnetic and electronic properties. Particularly noteworthy is the ultra-high vacuum and high magnetic field microscope, which can operate down to 1 K using a Joule–Thompson valve, allowing the study of atomic and molecular spins, under a cryomagnet of 1 T magnetic field. Prof. Bartolomé has recently contributed in this area [5]. 4. The creation of the Institute of Nanoscience and Materials of Aragon (INMA). There was an evolution in the research of new materials both at the ICMA and the INA, with strong collaboration between different research groups supported by the advantage of having unique infrastructures such as those established at the LMA. The overlapping of different research lines and the close collaboration generated by the new scientific capabilities allowed for the design of a new Institute. The INMA emerged with the institutional support of the University of Zaragoza and the CSIC, designing a new research center in 2020 as a result of the merger of the INA and the INMA. Currently, this Center brings together most of the knowledge in nanostructured materials in Aragon, and it has been recognized with the nomination as a “Severo Ochoa” Center of Excellence. Prof. J. Bartolomé has followed this process, supporting it and applying his knowledge and management experience. All of this has been reflected in his scientific output and the promotion of eminent researchers emerging from his research group. There is no doubt that research into materials from a nanoscopic point of view opens new avenues of knowledge that will solve important problems facing society today and that new technologies are demanding. I want to end this brief note by highlighting fantastic memories and experiences in remote places, coinciding at conferences or stays in Grenoble at the ILL, as well as excursions through the Pyrenees. For all this, you deserve these monographs in memory of your successful academic and research career. J. Bartolomé, J. A. Rojo, R. Navarro, D. Gonzalez, M. R. Ibarra, and A. Del Moral, Magnetoelastic phase transition in KMnF3, J. Magn. Magn. Mater. 31–34, 1052 (1983). B. M. R. Ibarra, P. A. Algarabel, A. Alberdi, J. Bartolomé, and A. del Moral, Citation, Magnetostriction and thermal expansion of RE2Fe1, J. Appl. Phys. 61, 3451 (1987). J. M. D. Coey and I. V. Mitchell, The Concerted European Action on Magnets (CEAM): a prototype for international scientific collaboration, Int. J. Technol. Manag. 6, 547 (1991). J. M. de Teresa, M. R. Ibarra, P. A. Algarabel, C. Ritter, C. Marquina, J. Blasco, J. Garcia, Al. del Moral, and Z. Arnold, Evidence for magnetic polarons in the magnetoresistive perovskites, Nature 386, 256 (1997). E. Bartolomé, J. Bartolomé, F. Sedona, J. Lobo-Checa, D. Forrer, J. Herrero-Albillos, M. Piantek, J. Herrero-Martín, D. Betto, E. Velez-Fort, L. M. García, M. Panighel, A. Mugarza, M. Sambi, and F. Bartolomé, Enhanced magnetism through oxygenation of FePc/Ag(110) monolayer phases, J. Phys. Chem. C 124, 13993 (2020).